Plasmacytoid urothelial carcinoma of renal pelvis with positive zinc finger E-box-binding homeobox 1: a case report - Atsuko Takada-Owada; Yumi Nozawa; Masato Onozaki; Shuhei Noda; Tsengelmaa Jamiyan; Yuumi Tokura; Yoshimasa Nakazato; Takao Kamai; Kazuyuki Ishida (BMC, 2020)
Abstract Background The tumor transformation mechanism of a plasmacytoid urothelial carcinoma remains unexplained. We describe the case of a plasmacytoid urothelial carcinoma of the renal pelvis in which the expression of zinc finger E-box-binding homeobox 1 (ZEB1), a key nuclear transcription factor in an epithelial-mesenchymal transition, is involved in tumor transformation. Case presentation The patient had a left nephrectomy with the clinical diagnosis of left pelvic renal cancer. The resected specimen showed that the tumor surface comprised a noninvasive papillary urothelial carcinoma with the carcinoma in situ, and the invasive area comprised a plasmacytoid urothelial carcinoma characterized by the presence of single dyscohesive malignant cells that resembled plasma cells in a loose myxoid stroma. The noninvasive urothelial carcinoma was positive for cytokeratin and E-cadherin, and negative for vimentin and ZEB1. In contrast, the invasive plasmacytoid urothelial carcinoma was positive for cytokeratin and also vimentin and ZEB1, and negative for E-cadherin. Additionally, this component was immunoreactive for CD138 and CD38 that are immunohistochemical markers for plasma cells. Conclusion We suggest that ZEB1 is involved in the plasmacytoid transformation by repressing the E-cadherin in a plasmacytoid urothelial carcinoma.